Measuring the vitality and effectiveness within Social sciences and humanities research: an attempt in Italian LIS studies - Turbanti, Simona (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
This study constitutes the beginning of a PhD research in Library and information science at Sapienza University of Rome, aimed at investigating the level of internationalisation, vitality and effectiveness of Italian Library and information studies.  The paper describes the methodology of search in international citational database, Web of science and Scopus, and in Google scholar for any scholarly work published by Italian LIS tenured researchers and university professors.  The results in WoS and Scopus are illustrated and compared with a first collection of data within Italian similar field of Social sciences and humanities (SSH). The reliability of the data collected in citation database within the areas of Social sciences and humanities and their significance are limited; also the comparison with Italian historical and paleographic fields seems to confirms that a substantial impact of SSH non-Anglophone scientific production within citational database is influenced by a number of factors (number of indexed core journals, language of publication, level of coverage of journals, etc.). On the other hand, Google scholar could be a valuable tool for humanistic fields, but it is necessary to deal with the complexity of the analysis and the problems of homonyms. Therefore, these first research results made it clear that, in order to investigate the presence and impact of Italian LIS studies, a correct use and organization of quantitative data is essential.